Ancient Christian commentary on Scripture ; NT v.II - Hall, Christopher A.; Oden, Thomas Clark, 1931- (Downers Grove, IL IVP, 2000)
Contents : v. II : Mark. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Mark -- commentaries; Fathers of the church; Bible. N.T. Mark -- criticism, interpretation, etc. -- History -- early church, ca. 30-600 -- sources